GROWTH PERFORMANCE OF DOMESTICATED ASIAN REDTAIL CATFISH Hemibagrus nemurus FINGERLINGS REARED AT DIFFERENT STOCKING DENSITIES - Otong Zenal Arifin; Vitas Atmadi Prakoso; Endang Haris Suhud; Jojo Subagja (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2020)
Asian redtail catfish Hemibagrus nemurus is one of the prospective aquaculture commodities in Indonesia. However, there are still shortcomings in completing the domestication of this species. As such, this study was conducted to observe the growth of Asian redtail catfish at different stocking densities. Fish (body weight (BW) of 21.62 ± 0.57 g) were stocked in nine different floating nets (dimension: 2 m x 2 m x 1 m) inside a concrete pond (40 m x 20 m) with three stocking density treatments (10, 15, and 20 fish/m3). Each treatment consisted of three replicates. Growth data were collected every 30 days during 120 days of rearing period which included weight gain (WG), specific growth rate in body weight (SGRBW), average daily growth (ADGBW), biomass gain (BG), feed conversion ratio (FCR), and survival rate (SR). Measured water quality parameters during the experiment consisted of temperature, pH, and dissolved oxygen. The results showed that the best growth performance was achieved by fish at the stocking density of 15 fish/m3 compared to that of fish with the stocking density of 10 and 20 fish/m3. The FCR value of fish at the stocking density of 15 fish/m3 was also significantly better than those of 10 fish/m3 and 20 fish/m3 (P<0.05). The survival rate in each treatment was not significantly different (P>0.05). This study suggests that the optimal stocking density for Asian redtail catfish fingerlings is 15 fish/m3, beyond that value, growth reduction might be expected. Further research is needed to observe its optimal stocking density in different culture systems.